Josephson effect and Andreev reflection in Ba1–xNaxFe2As2 (x = 0.25 and 0.35) point contacts: III Международный семинар по микроконтактной спектроскопииХарьков, Украина, 8–11 сентября 2014 г. - Fisun, V.V.; Balkashin, O.P.; Kvitnitskaya, O.E.; Korovkin, I.A.; Gamayunova, N.V.; Aswartham, S.; Wurmehl, S.; Naidyuk, Yu.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
I(V) characteristics and their first derivatives of ScS and ScN-type (S is superconductor, c is constriction, N is normal metal) point contacts (PCs) based on Ba1–xNaxFe2As2 (x = 0.25 and 0.35) were studied. ScS-type PCs with S = Nb,Ta, and Pb show Josephson-like resistively shunted I(V) curves with microwave induced Shapiro steps which satisfy relation 2eV = ћω. The IcRN product (Ic is critical current, RN is normal state PC resistance) in these PCs is found to be up to 1.2 mV. All this data with the observed dependence of the Ic on the microwave power of ScS PCs with Pb counterelectrode indicates the presence of the singlet s-wave type pairing in Ba1–xNaxFe2As2. From the dV/dI(V) curves of ScN-type PCs demonstrating Andreev-reflection like features, the superconducting gap Δ ratio 2Δ/kBTc = 3.6 ± 1 for the compound with x = 0.35 was evaluated. Analysis of these dV/dI(V) at high biases V, that is well above Δ, testifies transition to the thermal regime in PCs with a voltage increase.